2013
DOI: 10.1086/672372
|View full text |Cite
|
Sign up to set email alerts
|

Social Dominance Is Associated with Individual Differences in Heart Rate and Energetic Response to Food Restriction in Female Red Deer

Abstract: Energy expenditure is a key mechanism underlying animal ecology, yet why individuals often differ in metabolic rate even under identical conditions remains largely unexplained. Individual variation in metabolism might be explained by correlations with other behavioral and physiological traits, with individual syndromes having environment- or state-dependent costs and benefits to fitness. We tested whether social rank within herds of female red deer is associated with individual differences in resting heart rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In contrast, dominance was clearly positively correlated with RMR for both ectotherms and endotherms. Dominant individuals are often those that can acquire more resources (territory, food, or mates), and in accordance with the increased intake hypothesis, these individuals should be able to maintain high RMR in non-limiting conditions (Careau et al 2008;Careau and Garland 2012;Turbill et al 2013). However, the relatively large effect size may be inflated by early studies that found large effects from small samples (e.g., Røskaft et al 1986), as more recent studies with much larger samples sizes typically identify far smaller effects (e.g., Radwan et al 2004).…”
Section: Patterns Of Rmr Correlations With Fitness-related Traits Differ Markedly By Trait But Generally Support the Increased Intake Hypmentioning
confidence: 79%
“…In contrast, dominance was clearly positively correlated with RMR for both ectotherms and endotherms. Dominant individuals are often those that can acquire more resources (territory, food, or mates), and in accordance with the increased intake hypothesis, these individuals should be able to maintain high RMR in non-limiting conditions (Careau et al 2008;Careau and Garland 2012;Turbill et al 2013). However, the relatively large effect size may be inflated by early studies that found large effects from small samples (e.g., Røskaft et al 1986), as more recent studies with much larger samples sizes typically identify far smaller effects (e.g., Radwan et al 2004).…”
Section: Patterns Of Rmr Correlations With Fitness-related Traits Differ Markedly By Trait But Generally Support the Increased Intake Hypmentioning
confidence: 79%
“…Already the approach by a dominant group member and the associated risk of aggression were found to significantly increase heart rate in rhesus macaques [26], and even indirect social interactions can affect heart rate, for example observing aggressive interactions as a bystander [20,21], or visual and olfactory presentation of dominant or aggressive individuals [36,46]. The relationship between social status and heart rate can manifest itself in rank-dependent differences in resting heart rates, as described in red deer, Cervus elaphus , where subordinate individuals have lower resting heart rates compared to dominant individuals, which might result in a better capacity to minimize energy requirements [25].
Figure 1Examples of heart rate modulation in greylag geese.
…”
Section: Social Modulation Of Heart Ratementioning
confidence: 99%
“…[24]red deer, Cervus elaphus rumen-located transmittersTurbill et al . [25]rhesus macaques, Macaca mulatta implanted radio-transmitterAureli et al . [26]anthropogenic disturbanceAdélie penguins, Pygoscelis adeliae artificial eggsNimon et al .…”
Section: General Introductionmentioning
confidence: 99%
“…However, acclimatization to changing stressors and intraspecific differences in a population, in terms of social positioning, reproductive status, and age, may influence an individual's sensitivity and vulnerability to climate change. For example, when food was restricted, subordinate female red deer, surprisingly, achieved a much lower metabolic rate than did dominant females, resulting in less body mass loss [160]. On the other hand, vervet monkeys (Chlorocebus pygerythrus) with a greater number of social partners achieved better regulation of body temperature during winter than did those with fewer relationships [149].…”
Section: Behavioural Adjustmentsmentioning
confidence: 99%